Iloprost in Acute Post-kidney Transplant Atheroembolism: A Case Report of Two Successful Treatments - Corradetti, Valeria; Comai, Giorgia; Ravaioli, Matteo; Cuna, Vania; Aiello, Valeria; Odaldi, Federica; Angeletti, Andrea; Capelli, Irene; La Manna, Gaetano (Frontiers in Medicine, 2020)
Cholesterol embolization (CE) is a rare and alarming post-transplant complication, responsible for primary non-function (PNF) or delayed graft function (DGF). Its incidence is expected to rise due to increasingly old donors and recipients and the extended criteria for donation. Therapy with statins and steroids has not been shown to be effective, while agonism of prostaglandin I2 has been reported to be useful in systemic CE. We report two cases of acute post-transplant CE in which intravenous iloprost (0.05 mg/kg/day) was added to standard statin and steroid therapy. In the first instance, CE was due to embolization from the kidney artery resulting in embolization of the small vessels; after a long DGF and 15 days of iloprost therapy, renal function recovered. The second instance is a case of embolization from the iliac artery of the recipient, where CE manifested as a partial renal infarction. After 5 days of iloprost administration, creatinine levels improved. Iloprost acts on vasodilation and on different inflammatory pathways, improving the anti-inflammatory profile. Post-transplant CE is difficult to diagnose and, if not treated, can lead to loss of function. Iloprost added to standard therapy could be beneficial in accelerating renal function recovery immediately after transplant.